Political Intrigue and Power in the Novel Lambung Mangkurat by Randu Alamsyah Through Semiotic Studies - Dewi, Dwi Wahyu Candra; Hamlianor, Norlia (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to describe the content of the novel Lambung Mangkurat using the semiotic theory introduced by Charles Sanders Peirce as its analytical framework. This analytical approach involves the identification and discussion of icons, indices, and symbols present in the narrative of the novel. The study adopts a library research approach with a qualitative interpretive method. The data used comes from various primary and secondary sources, which are then interpreted descriptively. The data collection method in this study involves the use of documentation techniques and a review of library materials. The analysis results show that the spread of gossip in the Negara Dipa community about Lambung Mangkurat, who asks for toys from adults borrowing them, is an icon of Lambung Mangkurat's attitude when begging for the throne from Arya Megasari. On the other hand, the accusations and insults directed at Lambung Mangkurat represent an index of the political conspiracy designed by some officials of Negara Dipa to eliminate Lambung Mangkurat from the political arena in the region. Additionally, the slanderous actions by Arya Megasari and Tatah Jiwa to tarnish Lambung Mangkurat's reputation can be interpreted as a symbol of their hatred and fear towards Lambung Mangkurat's ambition to seize the throne of Empu Jatmika.